STUDI KELAYAKAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) DOMESTIK KAWASAN BENDUNG KOTA PALEMBANG - Edward Candra; Rosmalinda Permatasari; Leni Kurniati (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2023)
Sanitation is a way of treating household waste to prevent humans from being exposed to it, free of harmful impurities and waste materials. The use of wastewater treatment plants is expected to be able to reduce pollution produced by domestic activities. Since the last five years, the city of Palembang has had several WWTPs that process domestic waste, but there have been a few problems that have occurred so that a study of these problems is needed in the field. The research method used in this study uses both quantitative and qualitative research. The results showed that the percentage of IPAL Bendung was 11.7% of newly used WWTP capacity and 83.3% of WWTP idle capacity. This shows that the idle capacity of the two WWTP Bendungs is very high, and it is necessary to increase the house connection. Based on the results of the studies that have been found, the WWTP Bendungs found problems with discharge and detention time.